GarA is an essential regulator of metabolism in Mycobacterium tuberculosis. Issue 2 (8th September 2013) - Ventura, Marcello; Rieck, Barbara; Boldrin, Francesca; Degiacomi, Giulia; Bellinzoni, Marco; Barilone, Nathalie; Alzaidi, Faisal; Alzari, Pedro M.; Manganelli, Riccardo; O'Hare, Helen M.
Summary Alpha‐ketoglutarate is a key metabolic intermediate at the crossroads of carbon and nitrogen metabolism, whose fate is tightly regulated. In mycobacteria the protein GarA regulates the tricarboxylic acid cycle and glutamate synthesis by direct binding and regulation of three enzymes that use α‐ketoglutarate. GarA, in turn, is thought to be regulated via phosphorylation by protein kinase G and other kinases. We have investigated the requirement for GarA for metabolic regulation during growth in vitro and in macrophages. GarA was found to be essential to Mycobacterium tuberculosis, but dispensable in non‐pathogenic Mycobacterium smegmatis. Disruption of garA caused a distinctive, nutrient‐dependent phenotype, fitting with its proposed role in regulating glutamate metabolism. The data underline the importance of the TCA cycle and the balance with glutamate synthesis in M. tuberculosis and reveal vulnerability to disruption of these pathways.